FITOSOSIOLOGI HUTAN DI SEBAGIAN KAWASAN SUAKA MARGASATWA BUTON UTARA, SULAWESI TENGGARA - Mansur, Muhammad (Jurnal Teknologi Lingkungan, 2003)
The degradation rate of forest in the recent 5 years increases rapidly,particulartly in Sulawesi. The biggest damaged comes from the human impact,which spreads to the conservation area. As a result, the areais decreased,whereas its function and its potency have not been explored. The ecologicalresearch has been conducted in Soloi forest, Suaka Margasatwa Buton Utara inMay 2003. The objectives of this work are to study the condition, which belongto. 75 general and 35 families with density of trees are 277 individual (stemdiameter > 10 cm ), and 1140 sampling ( 2-9,9 cm stem diameter ). The foresttype is low land primary forest, which dominated by Casearia rugulosa,Diospyros pilosanthere, Cleistanthus myriantus, Canarium hirsutum, andDrypetes longifolia. In the forest structure, trees with 10-20 cm stem diameter isin the first rankwith the total number 57,02%, then followed by the trees with 20-30 cm diameter (20,22%). In general, the forest condition in research site isgood, although a few areas are damaged due to illegal loging.